Surgical stabilization of rib fractures (SSRF): the WSES and CWIS position paper - Giacomo Sermonesi; Riccardo Bertelli; Fredric M. Pieracci; Zsolt J. Balogh; Raul Coimbra; Joseph M. Galante; Andreas Hecker; Dieter Weber; Zachary M. Bauman; Susan Kartiko; Bhavik Patel; SarahAnn S. Whitbeck; et al. (World Journal of Emergency Surgery)
Abstract Background Rib fractures are one of the most common traumatic injuries and may result in significant morbidity and mortality. Despite growing evidence, technological advances and increasing acceptance, surgical stabilization of rib fractures (SSRF) remains not uniformly considered in trauma centers. Indications, contraindications, appropriate timing, surgical approaches and utilized implants are part of an ongoing debate. The present position paper, which is endorsed by the World Society of Emergency Surgery (WSES), and supported by the Chest Wall Injury Society, aims to provide a review of the literature investigating the use of SSRF in rib fracture management to develop graded position statements, providing an updated guide and reference for SSRF. Methods This position paper was developed according to the WSES methodology. A steering committee performed the literature review and drafted the position paper. An international panel of experts then critically revised the manuscript and discussed it in detail, to develop a consensus on the position statements. Results A total of 287 studies (systematic reviews, randomized clinical trial, prospective and retrospective comparative studies, case series, original articles) have been selected from an initial pool of 9928 studies. Thirty-nine graded position statements were put forward to address eight crucial aspects of SSRF: surgical indications, contraindications, optimal timing of surgery, preoperative imaging evaluation, rib fracture sites for surgical fixation, management of concurrent thoracic injuries, surgical approach, stabilization methods and material selection. Conclusion This consensus document addresses the key focus questions on surgical treatment of rib fractures. The expert recommendations clarify current evidences on SSRF indications, timing, operative planning, approaches and techniques, with the aim to guide clinicians in optimizing the management of rib fractures, to improve patient outcomes and direct future research.